A ANALISIS FOLKLOR SEBAGIAN LISAN PADA UPACARA ADAT BEGURU MASYARAKAT KABUPATEN BENER MERIAH - Ulina, Seri; Rani Ardesi Pratiwi; Safriandi (Global Action and Education for Society, 2026)
This study aims to describe the denotative meaning and connotative meaning contained in the beguru traditional ceremony of the people of Bener Meriah Regency. This type of research is qualitative. This research was conducted in Bener Meriah Regency from May to June 2025. The data of this research is in the form of sentences. The data source of this research is traditional leaders in Bener Meriah Regency. Data collection techniques in this research are observation, interviews, documentation and notes. Data analysis techniques in this research are data reduction, data presentation and conclusion. Based on the results of the study, seventy data were found which were divided into denotative meaning and connotative meaning, namely denotative meaning totaling 44 data and connotative meaning totaling 46 data.